The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11259-010-9397-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving calving management to further enhance reproductive performance in dairy cattle

Abstract: The aim of this study was to develop a system for the monitoring of calving to both reduce perinatal morta1ity and improve dairy cow fertility by preventing the majority of post-partum reproductive pathologies. Eighty dairy cows were assigned to the protocol of calving monitoring using GSM (Global System for Mobile Communications) technology. The application of GSM technology and the proper management of calving facilities comprise reliable approaches for calving assistance and improvements in reproductive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…Previous experience with equine alarm systems [18], which are maintained in site by suturing the device to the vulvar labia, have shown the occurrence of false alarms caused by the cow scratching in response to the suture. Moreover, the application of that system is cumbersome, requires the presence of a veterinary practitioner and would be disadvantageous economically for the dairy industry [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous experience with equine alarm systems [18], which are maintained in site by suturing the device to the vulvar labia, have shown the occurrence of false alarms caused by the cow scratching in response to the suture. Moreover, the application of that system is cumbersome, requires the presence of a veterinary practitioner and would be disadvantageous economically for the dairy industry [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the aim of this study was to evaluate the suitability of a remote calving alarm system applied in cattle, as previously described by Paolucci et al. (2010) and Palombi et al. (2013), in Mediterranean buffalo heifers from the functional and local tolerance point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have regarded the potential of improving calving management by using specialized calving sensors (Palombi, et al, 2013, Paolucci, et al, 2010. The sensitivity and specificity were not studied explicitly.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…This expelled module transmits a signal when it is outside the body (Palombi, et al, 2013). When this sensor system was applied on dairy farms studies reported a significant decrease on calf mortality, uterine infections and number of days open (Palombi, et al, 2013, Paolucci, et al, 2010. Secondly an existing sensor could be extended with an additional algorithm to detect calving, next to its original purpose.…”
Section: Introductionmentioning
confidence: 99%